EFFECT OF GROWTH PROMOTING SUBSTANCES ON THE FRUIT QUALITY OF REJUVENATED SAPOTA ORCHARD - D. DABERAO, MANGESH; JOSHI , P. S.; SATKAR, KUNTAL (The Bioscan, 2016)
Major degradation in the quality of the fruits of the sapota occurs due to less care of the orchard. The rejuvenation of the old orchard is very desirable for obtaining good yield with good quality fruits. Keeping this in view, the present study was conducted to study the effect of growth promoting substances on the fruit quality of rejuvenated sapota orchard. The rejuvenated sapota trees were treated with different concentrations of growth promoting substances i.e., GA3 and KNO3. The treatment T9 (2% KNO3+50 ppm GA3) gave the best quality fruits in the rejuvenated sapota orchard. Treatment T9 (2% KNO3+50 ppm GA3) shows maximum peel weight (18.30g), pulp weight (106.56 g), total soluble solids (22.150Brix), total sugars (19.01%)and seed weight (1.50g) whereas treatment T1 Control (No spray) gave minimum peel weight (12.13 g), pulp weight (67.660g), total soluble solids (17.120 Brix), total sugars (17.20%) and seed weight (1.23 g) and non significant results were observed for fruit moisture and acidity of the fruits.